Mitochondrial Reactive Oxygen Species and Their Contribution in Chronic Kidney Disease Progression Through Oxidative Stress - Tirichen, Hasna; Yaigoub, Hasnaa; Xu, Weiwei; Wu, Changxin; Li, Rongshan; Li, Yafeng (Frontiers in physiology, 2021)
Mitochondria are known to generate approximately 90% of cellular reactive oxygen species (ROS). The imbalance between mitochondrial reactive oxygen species (mtROS) production and removal due to overproduction of ROS and/or decreased antioxidants defense activity results in oxidative stress (OS), which leads to oxidative damage that affects several cellular components such as lipids, DNA, and proteins. Since the kidney is a highly energetic organ, it is more vulnerable to damage caused by OS and thus its contribution to the development and progression of chronic kidney disease (CKD). This article aims to review the contribution of mtROS and OS to CKD progression and kidney function deterioration.